2021
DOI: 10.1080/02640414.2021.1949114
|View full text |Cite
|
Sign up to set email alerts
|

Identifying childhood movement profiles and comparing differences in mathematical skills between clusters: A latent profile analysis

Abstract: The aims of this study were; 1) to identify different movement profiles in sixth graders, and 2) to investigate if there are differences in their mathematical basic (BasicMath) and problem solving (ProbSol) skills between existing movement profiles. The sample included 461 (223 girls, 238 boys) students with a mean age of 11.27 ± .32 years from southern and middle Finland. A latent profile analysis (LPA) revealed four movement profiles: "poor movers", "average movers", "skilled movers" and "expert movers". The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“… 25 Four movement profiles—which were ‘poor movers’ (27.9%, n = 129), ‘average movers’ (38.4%, n = 177), ‘skilled movers’ (18.9%, n = 87) and ‘expert movers’ (14.8%, n = 68)—were identified when focusing on the performance of leap, throw-catch, jump, push-up, sit-up tests. 26 The present study explored three patterns of children’s movement performance and originally identified the characteristics associated with different types of movement difficulties. The biggest cluster, LD (n = 131, 58.2%), received significantly higher probability of ‘no difficulties’ than the MD cluster (n = 68, 30.2%) for all nine items except flexibility.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Four movement profiles—which were ‘poor movers’ (27.9%, n = 129), ‘average movers’ (38.4%, n = 177), ‘skilled movers’ (18.9%, n = 87) and ‘expert movers’ (14.8%, n = 68)—were identified when focusing on the performance of leap, throw-catch, jump, push-up, sit-up tests. 26 The present study explored three patterns of children’s movement performance and originally identified the characteristics associated with different types of movement difficulties. The biggest cluster, LD (n = 131, 58.2%), received significantly higher probability of ‘no difficulties’ than the MD cluster (n = 68, 30.2%) for all nine items except flexibility.…”
Section: Discussionmentioning
confidence: 99%